Prevalence of Bullying among Nurses in a Tertiary Hospital, Bangalore - Cency Baburajan; Sakthi Arasu; Ramesh Naveen (Occupational Health and Safety Society of Nepal, 2019)
Background: In the last decade, research conducted in different countries has shown that bullying in the health care sector especially among nurses is a widespread and serious problem. Bullying of nurses at workplace affects their quality of life, hinders delivery of quality healthcare and contributes to increase in workplace stress. So, this study was conducted to assess the prevalence of work place bullying among nurses working in a tertiary care hospital in Bangalore. Methods: This study was conducted among 300 staff nurses providing in-patient services in a tertiary health care hospital located in Bangalore. The required sample was selected utilizing the documents maintained in the office of Chief of Nursing Services and using computer generated random numbers. The data was collected using self-administered questionnaire which comprised of socio-demographic factors and Negative Acts Questionnaire-Revised. Results: Among the 297 respondents, 26.9% were victims of bullying in the past six months according to Negative Acts Questionnaire-Revised (NAQ-R). Among the participants who were bullied, those exposed to work-related bullying, person-related bullying and physical intimidation were 80%, 60% and 21.3% respectively. Conclusion: This study suggests existence of work place bullying among nurses which can adversely affect their performance as health care professionals and their quality of personal life.